(untitled) (Journal of actual problems of jurisprudence, 2019)
The article is dedicated to the questions of moral relations like the part of the subject of civil regulation, which is not related to the property. Under the non-property rights and benefits, authors understand not have economic substance and are not separable from the personality of their wealth and media freedoms as the current legislation. Summing up the above, authors can say that the civil law at this stage of the legal regulation of personal relations only sets general provisions, which require further development and transformation into an independent branch of law which should be comprehensive integrative, nature, as it affects the relations of private-public character.